Platelet Activation and Thrombosis in COVID-19 - Iba, Toshiaki; Wada, Hideo; Levy, Jerrold H. (Seminars in Thrombosis and Hemostasis, 2022)
Although thrombosis frequently occurs in infectious diseases, the coagulopathy associated with COVID-19 has unique characteristics. Compared with bacterial sepsis, COVID-19-associated coagulopathy presents with minimal changes in platelet counts, normal prothrombin times, and increased D-dimer and fibrinogen levels. These differences can be explained by the distinct pathophysiology of the thromboinflammatory responses. In sepsis-induced coagulopathy, leukocytes are primarily responsible for the coagulopathy by expressing tissue factor, releasing neutrophil extracellular traps, multiple procoagulant substances, and systemic endothelial injury that is often associated with vasoplegia and shock. In COVID-19-associated coagulopathy, platelet activation is a major driver of inflammation/thrombogenesis and von Willebrand factor and platelet factor 4 are deeply involved in the pathogenesis. Although the initial responses are localized to the lung, they can spread systemically if the disease is severe. Since the platelets play major roles, arterial thrombosis is not uncommon in COVID-19. Despite platelet activation, platelet count is usually normal at presentation, but sensitive biomarkers including von Willebrand factor activity, soluble P-selectin, and soluble C-type lectin-like receptor-2 are elevated, and they increase as the disease progresses. Although the role of antiplatelet therapy is still unproven, current studies are ongoing to determine its potential effects.
Keywords: COVID-19; platelet; thrombosis; von Willebrand factor; platelet factor 4; P-selectin; C-type lectin-like receptor 2; antiplatelet